Pikes Peak : legends of America's mountain - McChristal, James (Raton, N.M. : Sierra Grande Press, 1999)
Based on newspaper reports, historic maps, books, and first-hand accounts, this slender volume chronicles the adventures and misadventures of the explorers, entrepreneurs, government personnel, and others who were drawn to the easternmost high peak of the Front Ranges of the Rocky Mountains. Includes b&w historical photos.
Includes bibliographical references (p. 121-129) and index.
75016
Keywords: Colorado Pikes Peak; Pikes Peak (Colo.) -- History -- Anecdotes